If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6g + 13 = 2f + -11 Reorder the terms: 13 + 6g = 2f + -11 Reorder the terms: 13 + 6g = -11 + 2f Solving 13 + 6g = -11 + 2f Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 6g = -11 + -13 + 2f Combine like terms: 13 + -13 = 0 0 + 6g = -11 + -13 + 2f 6g = -11 + -13 + 2f Combine like terms: -11 + -13 = -24 6g = -24 + 2f Divide each side by '6'. g = -4 + 0.3333333333f Simplifying g = -4 + 0.3333333333f
| (2x+7)=25 | | 4(3z-1)=6(3-z) | | -4(1-7x)-5=19 | | 4ln(x)=0 | | 6x+8-3x=12-13x-14 | | -9-2-1-64= | | -n+0.4n+1.8=-4.2 | | -5(8+m)=-20 | | 12=.30x | | -2z^3(6z^2-5z-4)=0 | | 12=-6(6+b) | | 8-4(2p-1)=45 | | 9+4a=1-2a | | 16-16x=-8x+8 | | -45=-(6x+3) | | 7-x-3x+2=-8x-8 | | (5x+7w-6)(7x-4w)=0 | | 8x+10=6(x+5) | | .75-17=-8 | | 2+3x=79.17 | | 2m+6=5m | | 4(x+4)=-12 | | x^2-2x+10= | | 8x+2y=29 | | -32t^2+55t-32=0 | | (2x+10)=3x | | 2x+3=79.17 | | 3x+2x+3= | | 18.82+(-1.19)+0.08= | | 6x-60=2100 | | 4-sec^2(x)=0 | | -32t^2+55t+4=36 |